2011
DOI: 10.1055/s-0031-1300134
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum Pain Plaster in Chronic Non-specific Low Back Pain

Abstract: Topically applied capsaicin (CAS 404-86-4) induces the release of substance P, a neurotransmitter, from sensory C-fibres. In addition, there is a specific blockade of transport and de-novo synthesis of substance P. As a result, repeated applications of capsaicin bring about a long lasting desensitisation to pain (increase of pain threshold). The desensitising effect is fully reversible. The confirmed pharmacodynamic actions and a number of double-blind clinical studies indicate that local capsicum preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
3
33
0
1
Order By: Relevance
“…Though statistically significant, these differences compared with placebo are very modest. These results were similar to those obtained with a similar capsaicin 8% patch in a similarly designed trial (Keitel et al, 2001). The most common adverse events were application site warmth or itching, although inflammatory contact eczema, urticaria, small hemorrhagic spots, vesiculation, and dermatitis have been reported in a small number of patients (Frerick et al, 2003;Keitel et al, 2001).…”
supporting
confidence: 86%
“…Though statistically significant, these differences compared with placebo are very modest. These results were similar to those obtained with a similar capsaicin 8% patch in a similarly designed trial (Keitel et al, 2001). The most common adverse events were application site warmth or itching, although inflammatory contact eczema, urticaria, small hemorrhagic spots, vesiculation, and dermatitis have been reported in a small number of patients (Frerick et al, 2003;Keitel et al, 2001).…”
supporting
confidence: 86%
“…In 154 patients with chronic non-specific LBP, response rates (!30% reduction in pain) after 3 weeks were significantly higher in the capsicum plaster group (60.8%) than in the placebo group (42.1%; p ¼ 0.0219) 109 . However, improvements in total movement and disability were small and not significantly greater than with placebo 109 . Given, the relative lack of systemic side effects with these topical agents, further studies investigating their use as first-line treatments are required.…”
Section: Topical Preparationsmentioning
confidence: 82%
“…Both of the reviews were published in the Cochrane library and had strong methods and were well reported. These reviews included several randomized controlled trials including a herbal medicine [19][20][21][22][23][24][25][26][27]. Our search for randomized controlled trials resulted in the identification of 149 titles and upon reviewing abstracts and full texts 145 were excluded for various reasons including: not being an RCT, not including a population suffering from chronic NSLBP, not testing an herbal medicine or nutritional supplement, or being included in one of the reviews above.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…This review also described another RCT ( N=154) which found that a plaster of Capsicum frutescens with 11 mg capsaicinoids reduces pain and improves function more than placebo for the treatment of acute episodes of chronic non-specific LBP in the shortterm [24]. Therefore there is limited evidence for Rado-Salil cream or a Capsicum plaster for reducing pain more than placebo in the treatment of acute non-specific LBP in the short-term.…”
Section: Capsicum Frutescens Versus Placebo [12]mentioning
confidence: 99%